Preparation method of degradable firework base

CN118896522BActive Publication Date: 2026-10-27HUNAN ZHONGZI TAILINGS NEW MATERIALS TECHNOLOGY RESEARCH INSTITUTE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410794964.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-19
Publication Date
2026-10-27
Estimated Expiration
2044-06-19

AI Technical Summary

Technical Problem

[0002]传统的组合烟花底座材料以纸张为主要原料,通过将大张纸裁剪成小块纸样,再将小块纸样逐层粘贴至一定厚度,利用人工或机械卷制成所需规格的纸筒;这种传统的制作工艺工序繁多、效率低、浪费材料,导致生产成本较高

Benefits of technology

[0020]与现有技术相比,本发明的有益效果包括:先将尾矿和第一水混合得到第一浆料,将多孔陶瓷、羧甲基纤维素钠和第二水混合得到第二浆料,多孔陶瓷与羧甲基纤维素钠混合能够借助多孔吸附羧甲基纤维素钠,之后将第一浆料和第二浆料混合,在羧甲基纤维素钠的作用下多孔陶瓷与尾矿物料形成预结合力,之后加入发泡剂混合得到第三浆料,发泡剂的加入便于在第三浆料中形成孔隙减轻成型后的烟花底座的重量,且确保各组分的均匀分布,之后孔隙较多的第三浆料进一步压制成型,之后养护得到所述可降解烟花底座,该可降解烟花底座品质稳定,且具有优异的抗压强度、较为合适的吸水率和较低的干密度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118896522B_ABST
    Figure CN118896522B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of degradable firework base, and belongs to the technical field of firework production. The preparation method of the degradable firework base comprises the following steps: S1, mixing tailings and first water to obtain first slurry; S2, mixing porous ceramic, sodium carboxymethyl cellulose and second water at 45-55 DEG C to obtain second slurry; S3, mixing the first slurry and the second slurry, and then adding a foaming agent to obtain third slurry; S4, injecting the third slurry into a firework base mold for compression molding, and then curing to obtain the degradable firework base. The prepared degradable firework base is stable in quality, has excellent compressive strength, appropriate water absorption and low dry density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fireworks production technology, specifically to a method for preparing a biodegradable fireworks base. Background Technology

[0002] Traditionally, the base material for combination fireworks is mainly paper. Large sheets of paper are cut into small pieces, and then the small pieces are pasted layer by layer to a certain thickness. The paper tubes are then rolled into the required size by hand or machine. This traditional manufacturing process is complicated, inefficient, and wasteful of materials, resulting in high production costs.

[0003] In existing technologies, waste plastic is used as the main base material, with rice husks added as filler. The mixture is then mixed in a rubber mixing machine to form a block base material, which is then molded into the shell of the required specifications for the fireworks shell. This base material can also be processed into fireworks tubes. The waste plastic is a thermoplastic and can also be used as an adhesive in the mixture of fireworks shell base materials. It is lightweight, high-strength, aesthetically pleasing, not easily deformed, and has no static electricity reaction. Furthermore, by using waste plastic and rice husks as base materials, it turns waste into treasure, saving a large amount of paper materials for the fireworks industry. Although it replaces traditional paper with waste plastic and rice husks, the difficulty in recycling and modifying waste plastics leads to unstable product quality and potential safety hazards.

[0004] Currently, the slurry and tailings generated during ore mining are generally abandoned, resulting in resource waste. How to use tailings to produce stable and biodegradable fireworks bases is a problem that existing technologies need to solve. Summary of the Invention

[0005] The purpose of this invention is to overcome the above-mentioned technical deficiencies and provide a method for preparing a biodegradable fireworks base, thereby solving the technical problem of how to produce a stable quality biodegradable fireworks base from tailings in the prior art.

[0006] To achieve the above-mentioned technical objectives, the present invention provides a method for preparing a biodegradable fireworks base, comprising the following steps:

[0007] S1. The tailings and first water are mixed to obtain the first slurry;

[0008] S2. The porous ceramic, sodium carboxymethyl cellulose, and second water are mixed at 45-55℃ to obtain the second slurry;

[0009] S3. Mix the first slurry and the second slurry, then add a foaming agent and mix to obtain the third slurry;

[0010] S4. The third slurry is injected into the firework base mold and pressed into shape, and then cured to obtain the biodegradable firework base.

[0011] In any embodiment, the raw materials, calculated according to the weight parts of each raw material, include: 200-300 parts tailings, 100-200 parts primary water, 30-50 parts porous ceramics, 10-20 parts sodium carboxymethyl cellulose, 10-20 parts secondary water, and 30-40 parts foaming agent.

[0012] In any embodiment, the porous ceramic is a modified porous ceramic, which is prepared by the following steps: mixing an ethanol solution and a KH570 silane coupling agent to obtain a mixture, immersing porous alumina, porous silica and sepiolite in the mixture, filtering, and then drying to obtain the modified porous ceramic.

[0013] In any embodiment, the mass ratio of the porous alumina, the porous silica, and the sepiolite is 1:(2-3):(1-2).

[0014] In any embodiment, the mass ratio of the ethanol solution to the KH570 silane coupling agent is 10:(2-3), and the volume concentration of the ethanol solution is 70-80%; the mass ratio of the porous alumina to the KH570 silane coupling agent is (2-3):(2-3).

[0015] In any embodiment, the immersion time is 30-60 minutes.

[0016] In any embodiment, the foaming agent is one or both of azodicarbonamide and calcium carbonate.

[0017] In any embodiment, the foaming agent is a mixture of azodicarbonamide and calcium carbonate; wherein the mass ratio of the azodicarbonamide to the calcium carbonate is 1:(2-4).

[0018] In any embodiment, in step S1, the tailings have a particle size of 100-150 mesh.

[0019] In any embodiment, in step S4, after molding, the biodegradable fireworks base is obtained by air-drying and curing for 4-6 hours.

[0020] Compared with the prior art, the beneficial effects of the present invention include: firstly, tailings and first water are mixed to obtain a first slurry; then, porous ceramics, sodium carboxymethyl cellulose, and second water are mixed to obtain a second slurry. The mixture of porous ceramics and sodium carboxymethyl cellulose can adsorb sodium carboxymethyl cellulose through pores. Then, the first slurry and the second slurry are mixed. Under the action of sodium carboxymethyl cellulose, the porous ceramics and tailings materials form a pre-bonding force. Then, a foaming agent is added and mixed to obtain a third slurry. The addition of the foaming agent facilitates the formation of pores in the third slurry, reducing the weight of the molded firework base and ensuring the uniform distribution of each component. Then, the third slurry with more pores is further pressed and molded, and then cured to obtain the biodegradable firework base. The biodegradable firework base has stable quality and excellent compressive strength, a suitable water absorption rate, and a low dry density. Attached Figure Description

[0021] Figure 1 This is a photograph of the biodegradable oxidation base obtained in Example 1 of the present invention. Detailed Implementation

[0022] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60–120 and 80–110 are listed for a specific parameter, it is understood that ranges of 60–110 and 80–120 are also expected. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1–3, 1–4, 1–5, 2–3, 2–4, and 2–5. In this application, unless otherwise stated, the numerical range "a–b" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0~5" indicates that all real numbers between "0~5" have been listed in this article; "0~5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0023] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0024] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0025] This specific embodiment provides a method for preparing a biodegradable fireworks base, including the following steps:

[0026] S1. The tailings and first water are mixed to obtain the first slurry; the tailings have a particle size of 100-150 mesh;

[0027] S2. The porous ceramic, sodium carboxymethyl cellulose, and second water are mixed at 45-55℃ to obtain the second slurry;

[0028] S3. Mix the first slurry and the second slurry, then add a foaming agent and mix to obtain the third slurry;

[0029] S4. Inject the third slurry into the firework base mold and press it into shape. Then, air dry and cure for 4-6 hours to obtain the biodegradable firework base.

[0030] In this specific embodiment, the raw materials, calculated according to the weight parts of each raw material, include: 200-300 parts of tailings, 100-200 parts of primary water, 30-50 parts of porous ceramics, 10-20 parts of sodium carboxymethyl cellulose, 10-20 parts of secondary water, and 30-40 parts of foaming agent; the foaming agent is one or both of azodicarbonamide and calcium carbonate.

[0031] In some embodiments, the porous ceramic is a modified porous ceramic, which is prepared by the following steps: mixing an ethanol solution and a KH570 silane coupling agent to obtain a mixed solution; immersing porous alumina, porous silica, and sepiolite in the mixed solution for 30-60 minutes; then filtering; and then drying to obtain the modified porous ceramic; the mass ratio of the porous alumina, the porous silica, and the sepiolite is 1:(2-3):(1-2); the mass ratio of the ethanol solution to the KH570 silane coupling agent is 10:(2-3); the volume concentration of the ethanol solution is 70-80%; and the mass ratio of the porous alumina to the KH570 silane coupling agent is (2-3):(2-3). The modified porous ceramic is loaded with KH570 silane coupling agent, which can effectively combine with sodium carboxymethyl cellulose to improve its bonding force, thereby improving the bonding force between the porous ceramic and tailings and increasing its strength. In addition, under the action of foaming agent, it can also ensure that the final biodegradable fireworks base has high strength.

[0032] In some preferred embodiments, the foaming agent is a mixture of azodicarbonamide and calcium carbonate; wherein the mass ratio of azodicarbonamide to calcium carbonate is 1:(2-4). The combined use of these two foaming agents is more beneficial for improving the strength of the fireworks base. This may be due to the fact that calcium carbonate itself has a certain loading effect, and the loaded azodicarbonamide synergistically foams, resulting in better foaming effect and thus promoting uniform distribution of the components and improving strength.

[0033] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0034] In this invention, the terms "some embodiments," "this embodiment," and examples are used to describe a subset of all possible embodiments. However, it is understood that "some embodiments" can be the same subset or different subsets of all possible embodiments and can be combined with each other without conflict.

[0035] If the application documents contain similar descriptions such as "first / second", the following explanation shall be added: In the following description, the terms "first / second / third" are used only to distinguish similar objects and do not represent a specific ordering of objects. It is understood that "first / second / third" may be interchanged in a specific order or sequence where permitted, so that the embodiments described herein can be implemented in an order other than that illustrated or described herein.

[0036] In this embodiment, the term "and / or" is merely a description of the relationship between related objects, indicating that there can be three relationships. For example, object A and / or object B can represent three situations: object A exists alone, object A and object B exist simultaneously, and object B exists alone.

[0037] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed in accordance with the techniques or conditions described in the literature in the art or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products, and the related equipment is general-purpose equipment of the prior art.

[0038] The tailings in the following examples are lithium tailings.

[0039] It should be noted that during the preparation process, the amount of each component to be weighed depends on the experimental requirements. One part can represent 1g, 10g, 500g, 1kg, 10kg or 50kg, etc. This invention does not impose any restrictions on this.

[0040] Example 1

[0041] This embodiment proposes a method for preparing a biodegradable fireworks base, including the following steps:

[0042] S1. Lithium tailings and first water are stirred and mixed to obtain a first slurry; the particle size of the lithium tailings is 100-150 mesh;

[0043] S2. The porous ceramic, sodium carboxymethyl cellulose, and second water are stirred and mixed at 45°C to obtain the second slurry;

[0044] S3. Mix the first slurry and the second slurry together, then add the foaming agent and mix to obtain the third slurry;

[0045] S4. The third slurry is injected into the firework base mold and pressed into shape. After drying and curing in the shade for 4 hours, the biodegradable firework base is obtained.

[0046] In this embodiment, the raw materials, calculated according to the weight parts of each raw material, include: 200 parts lithium tailings, 150 parts primary water, 30 parts porous ceramics, 15 parts sodium carboxymethyl cellulose, 15 parts secondary water, and 35 parts calcium carbonate.

[0047] In this embodiment, the porous ceramic is a modified porous ceramic, which is prepared by the following steps: an ethanol solution and a KH570 silane coupling agent are stirred and mixed to obtain a mixture; porous alumina, porous silica, and sepiolite are immersed in the mixture for 40 minutes, then filtered, and then dried to obtain the modified porous ceramic; the mass ratio of the porous alumina, porous silica, and sepiolite is 1:2:1; the mass ratio of the ethanol solution to the KH570 silane coupling agent is 5:1, and the volume concentration of the ethanol solution is 70%; the mass ratio of the porous alumina to the KH570 silane coupling agent is 2:3.

[0048] Figure 1 The image shows a photograph of the biodegradable fireworks base prepared in this embodiment. As can be seen from the image, the base has a uniform surface, few defects, and is sturdy.

[0049] Example 2

[0050] This embodiment proposes a method for preparing a biodegradable fireworks base, including the following steps:

[0051] S1. Lithium tailings and first water are stirred and mixed to obtain a first slurry; the particle size of the lithium tailings is 100-150 mesh;

[0052] S2. The porous ceramic, sodium carboxymethyl cellulose, and second water are stirred and mixed at 50°C to obtain the second slurry;

[0053] S3. Mix the first slurry and the second slurry together, then add the foaming agent and mix to obtain the third slurry;

[0054] S4. The third slurry is injected into the firework base mold and pressed into shape. After drying and curing in the shade for 6 hours, the biodegradable firework base is obtained.

[0055] In this embodiment, the raw materials, calculated according to the weight parts of each raw material, include: 250 parts lithium tailings, 200 parts primary water, 40 parts porous ceramics, 15 parts sodium carboxymethyl cellulose, 15 parts secondary water, and 35 parts foaming agent; the foaming agent is a mixture of azodicarbonamide and calcium carbonate; wherein the mass ratio of azodicarbonamide to calcium carbonate is 1:3.

[0056] In this embodiment, the porous ceramic is a modified porous ceramic, which is prepared by the following steps: an ethanol solution and a KH570 silane coupling agent are stirred and mixed to obtain a mixture; porous alumina, porous silica, and sepiolite are immersed in the mixture for 50 minutes, then filtered, and then dried to obtain the modified porous ceramic; the mass ratio of the porous alumina, porous silica, and sepiolite is 1:3:2; the mass ratio of the ethanol solution to the KH570 silane coupling agent is 10:3, and the volume concentration of the ethanol solution is 75%; the mass ratio of the porous alumina to the KH570 silane coupling agent is 3:2.

[0057] Example 3

[0058] This embodiment proposes a method for preparing a biodegradable fireworks base, including the following steps:

[0059] S1. Lithium tailings and first water are stirred and mixed to obtain a first slurry; the particle size of the lithium tailings is 100-150 mesh;

[0060] S2. The porous ceramic, sodium carboxymethyl cellulose, and second water are stirred and mixed at 50°C to obtain the second slurry;

[0061] S3. Mix the first slurry and the second slurry together, then add the foaming agent and mix to obtain the third slurry;

[0062] S4. The third slurry is injected into the firework base mold and pressed into shape. After drying and curing in the shade for 5 hours, the biodegradable firework base is obtained.

[0063] In this embodiment, the raw materials, calculated according to the weight parts of each raw material, include: 300 parts lithium tailings, 100 parts primary water, 40 parts porous ceramics, 10 parts sodium carboxymethyl cellulose, 20 parts secondary water, and 40 parts foaming agent; the foaming agent is a mixture of azodicarbonamide and calcium carbonate; wherein the mass ratio of azodicarbonamide to calcium carbonate is 1:2.

[0064] In this embodiment, the porous ceramic is a modified porous ceramic, which is prepared by the following steps: an ethanol solution and a KH570 silane coupling agent are stirred and mixed to obtain a mixture; porous alumina, porous silica, and sepiolite are immersed in the mixture for 60 minutes, then filtered, and then dried to obtain the modified porous ceramic; the mass ratio of the porous alumina, porous silica, and sepiolite is 1:2:2; the mass ratio of the ethanol solution to the KH570 silane coupling agent is 10:2.5, and the volume concentration of the ethanol solution is 75%; the mass ratio of the porous alumina to the KH570 silane coupling agent is 2:3.

[0065] Example 4

[0066] This embodiment proposes a method for preparing a biodegradable fireworks base, including the following steps:

[0067] S1. Lithium tailings and first water are stirred and mixed to obtain a first slurry; the particle size of the lithium tailings is 100-150 mesh;

[0068] S2. The porous ceramic, sodium carboxymethyl cellulose, and second water are stirred and mixed at 55°C to obtain the second slurry;

[0069] S3. Mix the first slurry and the second slurry together, then add the foaming agent and mix to obtain the third slurry;

[0070] S4. The third slurry is injected into the firework base mold and pressed into shape. After drying and curing in the shade for 5 hours, the biodegradable firework base is obtained.

[0071] In this embodiment, the raw materials, calculated according to the weight parts of each raw material, include: 300 parts lithium tailings, 100 parts primary water, 50 parts porous ceramics, 20 parts sodium carboxymethyl cellulose, 10 parts secondary water, and 30 parts foaming agent; the foaming agent is a mixture of azodicarbonamide and calcium carbonate; wherein the mass ratio of azodicarbonamide to calcium carbonate is 1:4.

[0072] In this embodiment, the porous ceramic is a modified porous ceramic, which is prepared by the following steps: an ethanol solution and a KH570 silane coupling agent are stirred and mixed to obtain a mixture; porous alumina, porous silica, and sepiolite are immersed in the mixture for 30 minutes, then filtered, and then dried to obtain the modified porous ceramic; the mass ratio of the porous alumina, porous silica, and sepiolite is 1:2:1; the mass ratio of the ethanol solution to the KH570 silane coupling agent is 10:3, and the volume concentration of the ethanol solution is 80%; the mass ratio of the porous alumina to the KH570 silane coupling agent is 3:2.

[0073] Example 5

[0074] The only difference between this embodiment and Embodiment 1 is that the foaming agent is azodicarbonamide; the other preparation methods and raw material amounts are the same as in Embodiment 1.

[0075] Comparative Example 1

[0076] The only difference between this comparative example and Example 2 is that the porous ceramic is the same amount of unmodified porous alumina, porous silica, and sepiolite used in Example 2.

[0077] Comparative Example 2

[0078] The difference between this comparative example and Example 2 lies in the order in which the foaming agent is added, as detailed below:

[0079] This comparative example presents a method for preparing a biodegradable fireworks base, comprising the following steps:

[0080] S1. Lithium tailings and first water are stirred and mixed, and then foaming agent is added and stirred to obtain the first slurry; the particle size of the lithium tailings is 100-150 mesh;

[0081] S2. The porous ceramic, sodium carboxymethyl cellulose, and second water are stirred and mixed at 50°C to obtain the second slurry;

[0082] S3. Mix the first slurry and the second slurry together, then add the foaming agent and mix to obtain the third slurry;

[0083] S4. The third slurry is injected into the firework base mold and pressed into shape. After drying and curing in the shade for 6 hours, the biodegradable firework base is obtained.

[0084] The amount of each component and its dosage are the same as in Example 2.

[0085] Comparative Example 3

[0086] The difference between this comparative example and Example 2 is that the materials were not added in sequence, but all the amounts were mixed and stirred at the same time to obtain a mixed slurry. The mixed slurry was injected into the firework base mold and pressed into shape, and then air-dried and cured for 6 hours to obtain the biodegradable firework base.

[0087] The compressive strength, water absorption rate, and dry density of the biodegradable firework bases prepared in Examples 1-4 and Comparative Examples 1-3 were tested, and the results are shown in Table 1. Water absorption rate test: The biodegradable firework bases were completely immersed in water for 24 hours, and then the bases were removed and air-dried. The water absorption rate of the bases was determined by weighing the difference in mass of the bases before and after immersion.

[0088] Comparative Example 4

[0089] The difference between this comparative example and Example 2 is that the raw material for the modified porous ceramic is not sepiolite. The preparation methods, raw materials, and quantities of the other biodegradable firework bases are the same as in Example 2. Specifically, the porous ceramic is a modified porous ceramic, which is prepared by the following steps: An ethanol solution and KH570 silane coupling agent are stirred and mixed to obtain a mixture; porous alumina and porous silica are immersed in the mixture for 50 minutes, then filtered, and then dried to obtain the modified porous ceramic. The quantities of porous alumina and porous silica are the same as in Example 2. The amount of sepiolite is compensated by a portion of porous alumina and a portion of porous silica, and the sum of the masses of the supplemented porous alumina and porous silica is the mass of the sepiolite.

[0090] Table 1 shows the compressive strength, water absorption rate, and dry density of the biodegradable firework bases prepared in Examples 1-4 and Comparative Examples 1-3.

[0091]

[0092]

[0093] As can be seen from Table 1, when only azodicarbonamide or calcium carbonate was used as a foaming agent in Examples 1 and 5, the compressive strength of the biodegradable firework base was poor. However, when both were used in combination, the compressive strength of the biodegradable firework base was higher. This may be because the combination of the two can improve the uniformity of the components in the slurry, thereby improving its compressive strength.

[0094] Comparative Example 1 exhibits lower compressive strength, lower water absorption, and higher dry density. This may be because the unmodified porous alumina, porous silica, and sepiolite do not carry coupling agents, resulting in relatively poor bonding strength with sodium carboxymethyl cellulose, and consequently, poor bonding strength with tailings. Under the action of foaming agents, the bonding strength is more easily weakened, leading to uneven component distribution, which in turn affects the foaming effect, resulting in lower compressive strength, lower water absorption, and higher dry density.

[0095] The main reason for the higher dry density of Comparative Example 2 is that the foaming agent was added too early, resulting in poor foaming effect and high dry density of the material.

[0096] When Comparative Example 3 is mixed together, the components are difficult to distribute evenly, resulting in poor compressive strength.

[0097] In Comparative Example 4, the strength actually decreased in the absence of sepiolite. This may be because the sepiolite in this invention absorbs water and softens, and its binding with tailings through sodium carboxymethyl cellulose significantly improves the mutual bonding force of each component. After drying, it hardens, thereby significantly improving the strength.

[0098] The biodegradable fireworks base proposed in this invention has a certain moisture-proof function, is fire-resistant, has high strength, and its suitable water absorption rate ensures that it has a certain moisture-proof function and can degrade into powder in nature.

[0099] The specific embodiments of the present invention described above do not constitute a limitation on the scope of protection of the present invention. Any other corresponding changes and modifications made in accordance with the technical concept of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a biodegradable fireworks base, characterized in that, Includes the following steps: S1. The tailings and first water are mixed to obtain the first slurry; S2. The porous ceramic, sodium carboxymethyl cellulose, and second water are mixed at 45-55℃ to obtain the second slurry; S3. Mix the first slurry and the second slurry, then add a foaming agent and mix to obtain the third slurry; S4. The third slurry is injected into the firework base mold and pressed into shape, and then cured to obtain the biodegradable firework base; The raw materials, calculated by weight, include: 200-300 parts tailings, 100-200 parts primary water, 30-50 parts porous ceramics, 10-20 parts sodium carboxymethyl cellulose, 10-20 parts secondary water, and 30-40 parts foaming agent. The porous ceramic is a modified porous ceramic, which is prepared by the following steps: mixing an ethanol solution and a KH570 silane coupling agent to obtain a mixed solution, immersing porous alumina, porous silica and sepiolite in the mixed solution, filtering, and then drying to obtain the modified porous ceramic. The tailings are lithium tailings.

2. The method for preparing the biodegradable fireworks base according to claim 1, characterized in that, The mass ratio of the porous alumina, the porous silica, and the sepiolite is 1:(2-3):(1-2).

3. The method for preparing the biodegradable fireworks base according to claim 1, characterized in that, The mass ratio of the ethanol solution to the KH570 silane coupling agent is 10:(2-3), and the volume concentration of the ethanol solution is 70-80%; the mass ratio of the porous alumina to the KH570 silane coupling agent is (2-3):(2-3).

4. The method for preparing the biodegradable fireworks base according to claim 1, characterized in that, The immersion time is 30-60 minutes.

5. The method for preparing the biodegradable fireworks base according to claim 1, characterized in that, The foaming agent is one or both of azodicarbonamide and calcium carbonate.

6. The method for preparing the biodegradable fireworks base according to claim 5, characterized in that, The foaming agent is a mixture of azodicarbonamide and calcium carbonate; wherein the mass ratio of azodicarbonamide to calcium carbonate is 1:(2-4).

7. The method for preparing the biodegradable fireworks base according to claim 1, characterized in that, In step S1, the tailings have a particle size of 100-150 mesh.

8. The method for preparing the biodegradable fireworks base according to claim 1, characterized in that, In step S4, after molding, the biodegradable fireworks base is obtained by air-drying for 4-6 hours.

Citation Information

Patent Citations

  • Firework set-off barrel and manufacturing method thereof

    CN103787619A

  • Granite waste stone dust foam ceramics and preparation method thereof

    CN107586102A